Matematik und philosophie : philosophischer kreis Wien - Istanbul = Matematik ve felsefe : Viyana - İstanbul felsefe çevresi = Mathematatics and philosophy : Vienna - Istanbul philosophy circle (İstanbul)
xiii, 153 .